Learning clinical reasoning in the workplace: a student perspective - Larissa IA Ruczynski; Marjolein HJ van de Pol; Bas JJW Schouwenberg; Roland FJM Laan; Cornelia RMG Fluit (BMC Medical Education, 2022)
Abstract Introduction Clinical reasoning is a core competency for every physician, as well as one of the most complex skills to learn. This study aims to provide insight into the perspective of learners by asking students about their own experiences with learning clinical reasoning throughout the medical Master’s curriculum. Methods We adopted a constructivist approach to organise three semi-structured focus groups within the Master’s curriculum at the medical school of the Radboud University Medical Center in Nijmegen (Netherlands) between August and December 2019. Analysis was performed through template analysis. Results The study included 18 participants who (1) defined and interpreted clinical reasoning, (2) assessed the teaching methods and (3) discussed how they used their context in order to learn and perform clinical reasoning during their clinical rotations. They referred to a variety of contexts, including the clinical environment and various actors within it (e.g. supervisors, peers and patients). Conclusion With regard to the process by which medical students learn clinical reasoning in practice, this study stresses the importance of integrating context into the clinical reasoning process and the manner in which it is learnt. The full incorporation of the benefits of dialogue with the practice of clinical reasoning will require additional attention to educational interventions that empower students to (1) start conversations with their supervisors; (2) increase their engagement in peer and patient learning; (3) recognise bias and copy patterns in their learning process; and (4) embrace and propagate their role as boundary crossers.